2011
DOI: 10.1523/jneurosci.5300-09.2011
|View full text |Cite
|
Sign up to set email alerts
|

Infragranular Sources of Sustained Local Field Potential Responses in Macaque Primary Visual Cortex

Abstract: A local field potential (LFP) response can be measured throughout the visual cortex in response to the abrupt appearance of a visual stimulus. Averaging LFP responses to many stimulus presentations isolates transient, phase-locked components of the response that are consistent from trial to trial. However, stimulus responses are also composed of sustained components, which differ in their phase from trial to trial and therefore must be evaluated using other methods, such as computing the power of the response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
112
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(127 citation statements)
references
References 48 publications
12
112
3
Order By: Relevance
“…For the trialby-trial correlation, we did not observe a correlation in the same frequency range. The results for this frequency band were, however, in line with previous findings that β-band EEG power is anticorrelated to the BOLD signal (24,27) and is predominantly measured in the LFP recorded from infragranular layers in nonhuman animals (8). The deep layers are therefore also a likely source for the β-attention effect in the EEG measured here.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For the trialby-trial correlation, we did not observe a correlation in the same frequency range. The results for this frequency band were, however, in line with previous findings that β-band EEG power is anticorrelated to the BOLD signal (24,27) and is predominantly measured in the LFP recorded from infragranular layers in nonhuman animals (8). The deep layers are therefore also a likely source for the β-attention effect in the EEG measured here.…”
Section: Discussionsupporting
confidence: 92%
“…For the β-band, we observed a negative correlation in deep layers that is particularly strong in V1 and V2. This finding corresponds with laminar recordings in animals that find the strongest β-band synchronization in deep layers (8). Furthermore, β-activity in early visual regions has been associated with top-down streams of information from higher order regions (2,3,48,51).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, recent neurophysiological work has indicated that gamma-band oscillations are particularly strong in superficial layers of the cortical column (Lakatos et al, 2005;Maier et al, 2010Maier et al, , 2011. These superficial layers have dense "forward" connections to higher-order areas (Thomson and Bannister, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have studied V1 laminar variation (5,8,9,25,(47)(48)(49) by using spike-field coherence analysis (25), current source density analysis (5,49,50), or the BOLD signal in functional MRI (47). In this study, we used drifting gratings with spatial frequency equal to two cycles per degree, which are optimal stimuli for stimulating neurons in the V1 network (20,51).…”
Section: Dynamics Of γ-Band Power At Different Cortical Depths In V1mentioning
confidence: 99%